An Inter- and Intra-Subject Transfer Calibration Scheme for Improving Feedback Performance of Sensorimotor Rhythm-Based BCI Rehabilitation - Cao, Lei; Chen, Shugeng; Jia, Jie; Fan, Chunjiang; Wang, Haoran; Xu, Zhixiong (Frontiers in Neuroscience, 2021)
Brain Computer Interface (BCI) system is a typical neurophysiological application to help paralyzed patients for human-machine communication. Stroke patients with motor disabilities are able to perform BCI tasks for clinical rehabilitation. This paper proposed an effective scheme of transfer calibration for BCI rehabilitation. The inter- and intra-subject transfer learning approaches could improve the low-precision classification performance for experimental feedback. The results implied that the systematical scheme was positive for increasing the confidence of voluntary training for stroke patients. In addition, it also reduced the time consumption of classifier calibration.